ANALYSIS OF THE INFLUENCE OF ECONOMIC AND ADMINISTRATIVE INFRASTRUCTURE ON ECONOMIC GROWTH OF PROVINCES OUTSIDE JAVA ISLAND - Grahita Dara Miartha; Sri Subanti (Journal of Mathematics and Mathematics Education, 2024)
This study aims to determine the effect of economic and administrative infrastructure on economic growth in provinces outside Java. The type of data used in this study is secondary data obtained from the Central Statistics Agency (BPS). The data used is time series data from 2019-2021 and cross section data for provinces outside Java Island. The analysis used is panel data regression using the Error Generalized Least Square (EGLS) method with cross section weight and cross sectin seemingly unrelated residual / SUR (PSCE). To estimate panel data regression, there are three approaches, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), Random Effect Model (REM). The data analysis procedure uses the Classical Assumption Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test and Hypothesis Test,  t test, F test and Coefficient of Determination. The results explained that Safe Drinking Water (X1) and Telephone Subscription (X4) had a positive and significant effect on the economic growth of provinces outside Java Island, while Road Facilities (X2), Distributed Electricity (X3) and Realization of Domestic Investment (X5) had a negative and significant effect on the economic growth of provinces outside Java Island with a coefficient of determination of 99.9%.